The hexane fraction of Ardisia crispa Thunb. A. DC. roots inhibits inflammation-induced angiogenesis - Dayang Erna Zulaikha, Awang Hamsin; Roslida, Abdul Hamid; Latifah, Saiful Yazan; Che Norma, Mat Taib; Yeong, Looi Ting (BioMed Central, 2013)
Background: Ardisia crispa (Myrsinaceae) is used in traditional Malay medicine to treat various ailments associated with inflammation, including rheumatism. The plant's hexane fraction was previously shown to inhibit several diseases associated with inflammation. As there is a strong correlation between inflammation and angiogenesis, we conducted the present study to investigate the anti-angiogenic effects of the plant's roots in animal models of inflammation-induced angiogenesis.Methods: We first performed phytochemical screening and high-performance liquid chromatography (HPLC) fingerprinting of the hexane fraction of Ardisia crispa roots ethanolic extract (ACRH) and its quinone-rich fraction (QRF). The anti-inflammatory properties of ACRH and QRF were tested using the Miles vascular permeability assay and the murine air pouch granuloma model following oral administration at various doses.Results: Preliminary phytochemical screening of ACRH revealed the presence of flavonoids, triterpenes, and tannins. The QRF was separated from ACRH (38.38% w/w) by column chromatography, and was isolated to yield a benzoquinonoid compound. The ACRH and QRF were quantified by HPLC. The LD50 value of ACRH was 617.02 mg/kg. In the Miles vascular permeability assay, the lowest dose of ACRH (10 mg/kg) and all doses of QRF significantly reduced vascular endothelial growth factor (VEGF)-induced hyperpermeability, when compared with the vehicle control. In the murine air pouch granuloma model, ACRH and QRF both displayed significant and dose-dependent anti-inflammatory effects, without granuloma weight. ACRH and QRF significantly reduced the vascular index, but not granuloma tissue weight.Conclusions: In conclusion, both ACRH and QRF showed potential anti-inflammatory properties in a model of inflammation-induced angiogenesis model, demonstrating their potential anti-angiogenic properties